PENGARUH GERAKAN GO GREEN SCHOOL TERHADAP PEMBENTUKAN KARAKTER PEDULI LINGKUNGAN SISWA DI MTsN MODEL KUOK KECAMATAN KUOK KABUPATEN KAMPAR - Mardliyah, Khasanatul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research by environmental damage, mainly in the province of Riau forest fires annually resulting in smoke that interfere with human health and activity. Schools have a major role in shaping the character of students, one of which is the character of environmental care. Students involved with activities Go Green School which is a program to instill character environmentally conscious students. The problems of the study are how the Go Green School movement towards the formation of character care about the environment a students Model Kuok Kuok District of Kampar regency. The purpose of this research is to determine the effect of Go Green School movement towards the formation of character care about the environment a students Model Kuok Kuok District of Kampar regency. This research is useful for the reader to add insight and information about education. This research method is quantitative descriptive. Data collection instruments used in this study is a questionnaire consisting of 34 questions about the influence of the movement Go Green School (variable X) and 39 questions of character formation caring environment (variable Y). Data was analyzed using simple linear regression. Thus the hypothesis that